The Effect of a Training Program on the Diabetic Patients Utilizing Skills of Insulin Injection Technique - Saad Hussein Murad (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study aims to evaluate patients’ performance toward insulin injection after training program toidentify the variation in skill of patients in insulin injection technique with regard to some variable (i.e.educational level and duration of insulin injection.Methodology: A quasi experimental study has been conducted on diabetic patients.An observational checklist had been prepared which consisted of 4 main areas with 37 sub-items, which aresyringe preparation for injection, insulin drawing; skin preparation for injection and insulin injection. Each of thesub-items has 2 options yes or no. One score for positive answer and zero for no.The sample of the study consisted of (n =30) males and females patients with Type 1 diabetes mellitus, whowere chosen randomly from AL-Wafa’a center for diabetic treatment in Mosul-Iraq during Dec. 2003.Results: The results of the study showed that the skills performance of insulin injection was statisticallydifferent in pre from post-test (49.37%, 76.67%) respectively by using X ), the result showed significantdifference at (P